The Prevalence and Risk Factors of Osteoporosis and Osteopenia in Patients Aged more than 50 Years, and Adherence to Osteoporosis Treatment Guideline in a Governmental Hospital in Al-Kharj, Saudi Arabia - Daud, Nur Aizati Athirah (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: Osteoporosis and osteopenia are common in Saudi Arabia and the burden of management in an aging population will increase in the coming decades. The study aimed to describe the prevalence of osteoporosis and osteopenia among patients more than 50 years old, and identify the risk factors of these conditions, as well as the adherence to the guideline for treating osteoporosis in a government hospital in Al-Kharj, Saudi Arabia. Methods: This is a retrospective and case–control study performed at an orthopedic clinic in King Khaled hospital from January 2020 to February 2021. Data were collected retrospectively from the electronic medical records. Results: During the study period, 752 patients visited the orthopedic clinic with a mean age of 69.05 (±13.575). About 13.6% of them were diagnosed with osteoporosis and 15.7% of them were diagnosed with osteopenia. The risk factors of having osteoporosis among the study population include being female (Odds Radio = 3.107, P = 0.001), having Vitamin D deficiency (OR = 21.447, P = 0.001), and having osteoarthritis (OR = 0.459, P = 0.006). The risk factors of having osteopenia among the study population include being female (OR = 2.003, P = 0.82), having Vitamin D deficiency (OR = 32.657, P = 0.001), and having osteoarthritis (OR = 6.185, P = 0.001). In the present study, 97.1% of the patients used an appropriate drug that is recommended by the reference guideline. Conclusions: Osteoporosis and osteopenia are quite prevalent among the study population. As an early intervention, screening for osteoporosis and Vitamin D levels may be proposed among Saudi individuals aged more than 50 years.